Inernet of Everything: A Solution to Mobile Banking using Voice Recognition (Global Journal of Computer Science and Technology, 2022)
The advancement in banking transaction system over the years has been enormous and the needs for identifications of customer s authentication validation and confirmation are of utmost priority and should be dealt with judiciously Mobile banking has emerged as one of the main division in digital world of financial transactions and consists of information inquiry notifications and alerts applications and payment transfer Mobile based application is used for connecting customer handset with bank server for all such services in the banking industry The current trend of Mobile banking as gone beyond the use of One Time Password OTP applications used by banks The problem with current banking applications is that they send data directly to customer in plain text form compromising with security recognised as OTP in most of the online transaction An online banking customer logging in to the bank s website with username and password triggers a request to send an OTP to his or her registered mobile phone or the OTP may not be necessary after one or two transaction There is every likely hold of Mobile phone been stealing access by unauthorised person or being hacked Upon receipt of a text message with the OTP the customer enters it with an additional field on the banking site s login page to complete the login process since your details are already on your phone It could have been fine if the mobile network can act immediately but blocking of network provider involves the presentation of National Identification Number NIN which is a chain reaction The purpose of this research work is to provide cost effective secure fast Mobile banking solution combining features of cryptography as well as behavioural pattern and Interactive Voice Response for final authentication and authorisation of costumer identification in all form of financial transactions